A discernment of prey selection by the ancient Maya: white-tailed deer (Odocoileus virginianus) pest, prey, or domesticate - Cantryll-Stewart, Ricki (2018)
This thesis investigates the demographics of paleo-populations of white-tailed deer (Odocoileus virginianus) as a means of testing the hypothesis that this species was domesticated or managed as a vital cultural and economic resource by the ancient Maya in Mesoamerica. To do so it employs a set of standardized bone measurements derived from a modern population and compares them with 1100 deer bone samples recovered by archaeologists from Maya sites dating from 450 B.C. to the late 16th century. These measurements were also applied to modern white-tailed deer specimens representing a discrete population from south eastern Florida of know age, and sex, for use as a baseline. The recorded measurements were used for side by side comparisons and to generate log ratios testing population stature and sexual dimorphism represented in the archaeological materials. Changes in deer stature and mortality profile over time are examined and tested against standard methods for the detection of herd management strategies, that may potentially reveal deer domestication or resource management. Pathologies common to white-tailed deer are identified and their potential for assessing the ontological age of mature deer is investigated. The results show variations in white-tailed deer stature over time and space, suggesting dynamic alterations in prey selection that may be reflective of changes in Maya social complexity.